PENGARUH DESAIN PRODUK DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA PT. MAP AKTIF ADIPERKASA DI MEDAN - Sitorus, Udur Marito; Asnawi, M; Firah, Al (Universitas Dharmawangsa, 2024)
This research aims to determine the influence of product design and product quality on purchasing decisions at PT. Adiperkasa Active MAP. The method used is Probability Sampling, and the techniques used are Stratified Random Sampling and Simple Random Sampling. The results of the t test for the product design variable (X1) are tcount = 0.779 and ttable = 1.984, so tcount < ttable then H0 is accepted and H1 is rejected. This means that partially the product design variable does not have a significant positive influence on consumer purchasing decisions at PT. Adiperkasa Active Map in Medan. The results of the t test on the product quality variable (X2) are tcount = 2.659 and ttable = 1.984, so tcount > ttable then H0 is rejected and H1 is accepted. This means that partially the product quality variable has a significant positive influence on consumer purchasing decisions at PT. Adiperkasa Active Map in Medan. The results of the F test show that the value of Fcount > Ftable = 9.780 > 3.091 so that it can be concluded that simultaneously, product design and product quality have a significant influence on purchasing decisions at PT. Adiperkasa Active Map in Medan. The R test results show the Adjusted R Square value = 0.169 (16.9%) while 83.1% is influenced by other factors that are outside the model and cannot be detected in this research.